Epidemiological assessment of SARS-CoV-2 reinfection. (October 2022) - Almadhi, Marwa; Alsayyad, Adel Salman; Conroy, Ronan; Atkin, Stephen; Awadhi, Abdulla Al; Al-Tawfiq, Jaffar A.; AlQahtani, Manaf
Highlights: Reinfection episodes were highest among those 30-39 years of age Most reinfection episodes occurred ≥9 months after initial infection Most individuals were asymptomatic during both episodes Vaccinated individuals were less likely to have symptomatic reinfection ( P  = 0.004) Only 6.6% of reinfection cases required hospitalization, and no deaths were recorded Abstract: Objectives: SARS-CoV-2 vaccination has been shown to reduce infection severity; however, the reinfection frequency among unvaccinated, partially vaccinated, and fully vaccinated individuals remains unclear. This study aims to elucidate the rates of and factors associated with such occurrences. Methods: This retrospective epidemiological report included 1362 COVID-19 reinfection cases in Bahrain between April 2020 and July 2021. We analyzed differences in disease severity and reinfection characteristics among various vaccination statuses: fully vaccinated, interrupted vaccination, one-dose vaccination, postreinfection vaccination, and unvaccinated. Results: Reinfection cases increased from zero per month in April-June 2020 to a sharp peak of 579 in May 2021. A significantly larger proportion of reinfected individuals were male (60.3%, P <0.0001). Reinfection episodes were highest among those 30-39 years of age (29.7%). The fewest reinfection episodes occurred at 3-6 months after the first infection (20.6%) and most occurred ≥9 months after the initial infection (46.4%). Most individuals were asymptomatic during both episodes (35.7%). Reinfection disease severity was mild, with vaccinated patients less likely to have symptomatic reinfection (odds ratio 0.71, P  = 0.004). Only 6.6% of reinfected patients required hospitalization. One death was recorded; the patient belonged to the unvaccinated group. Conclusion: Vaccine-induced immunity and previous infection with or without vaccination were effective in reducing reinfection disease severity.